Organic–inorganic bismuth (III)-based material: A lead-free, air-stable and solution-processable light-absorber beyond organolead perovskites - Lyu, Miaoqiang; Yun, Jung-Ho; Cai, Molang; Jiao, Yalong; Bernhardt, Paul V.; Zhang, Meng; Wang, Qiong; Du, Aijun; Wang, Hongxia; Liu, Gang; Wang, Lianzhou (Nano research, 2016)
Methylammonium bismuth (III) iodide single crystals and films have been developed and investigated. We have further presented the first demonstration of using this organic–inorganic bismuth-based material to replace lead/tin-based perovskite materials in solution-processable solar cells. The organic–inorganic bismuth-based material has advantages of non-toxicity, ambient stability, and low-temperature solution-processability, which provides a promising solution to address the toxicity and stability challenges in organolead- and organotin-based perovskite solar cells. We also demonstrated that trivalent metal cation-based organic–inorganic hybrid materials can exhibit photovoltaic effect, which may inspire more research work on developing and applying organic-inorganic hybrid materials beyond divalent metal cations (Pb (II) and Sn (II)) for solar energy applications.